MEASURES TO SUPPORT IMPLEMENTATION OF NEW IRRIGATION TECHNOLOGIES (British Journal of Global Ecology and Sustainable Development, 2022)
This article provides information on measures to improve land use and land with reduced productivity. The information provided in this article can be used to improve soils with reduced soil fertility. Encouraging activities such as further increasing soil fertility and productivity, transition to new irrigation technologies, establishment of plant protection services, involvement of modern laboratories and technologies, training of farmers is effective. Information is presented on the important processes of increasing soil fertility by introducing the mechanism. In addition, a set of measures used to improve soil fertility is mentioned.